PENERAPAN DIVERSI PADA TINGKAT PENUNTUT UMUM TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA MENURUT UU NO 11 TAHUN 2012 (Studi Kasus di Cabang Kejaksaan Negeri Padangsidimpuan di Sibuhuan) - Renhard Harve; Marlina Marlina; Muhammad Ekaputra; Edy Ikhsan (USU LAW JOURNAL, 2016)
A child is a nation’s next generation in which since a fetus until it is born it has its own right. As good citizens, we have to take our children, and this globalization era with it transparent information and technology, children will easily watch adult show in printed and electronic media so that their minds are   contaminated with adult presentation such as violence and amoral. This condition has caused a child to be involved in legal problems. The problems of the research were as follows: why a child that is in conflict with legal act should belong to Diversion system, how about the implementation of diversion process in the level of Prosecutors toward a child who was in conflict with law in the Attorney’s Office of Padangsidimpuan at Sibuhuan, and what obstacles which existed in the implementation of Diversion in the Attorney’s Office of Padangsidimpuan at Sibuhuan. The objective of the research was to analyze why a child who had a conflict with law should be implemented Diversion system, to find out the implementation of law enforcers toward a child who was in conflict with law in the Attorney’s Office of Padangsidimpuan, at Sibuhuan, and to find out the obstacles in implementing Diversion in the level of Attorney’s Office of Padangsidimpuan at Sibuhuan. The research used judicial normative and descriptive analytic approaches. The result of the research showed that the imposition of Law No. 11/2012 on the Process of Diversion in Children who did criminal acts would protect children in the process of criminal cases and support general prosecutors to prioritize the process of Diversion rather than the process of hearing in the Courts. Keywords: Diversion, Children who do Criminal Acts, Law Enforcers